De novo sequencing, assembly, and characterization of Asparagus racemosus transcriptome and analysis of expression profile of genes involved in the flavonoid biosynthesis pathway - Malik, Chanchal; Dwivedi, Sudhanshu; Rabuma, Tilahun; Kumar, Ravinder; Singh, Nitesh; Kumar, Anil; Yogi, Rajesh; Chhokar, Vinod (Frontiers in Genetics, 2023)
Asparagus racemosus is known for its diverse content of secondary metabolites, i.e., saponins, alkaloids, and a wide range of flavonoids. Flavonoids, including phenols and polyphenols, have a significant role in plant physiology and are synthesized in several tissues. Despite the diverse role of flavonoids, genetic information is limited for flavonoid biosynthesis pathways in A. racemosus.The current study explores full-scale functional genomics information of A. racemosus by de novo transcriptome sequencing using Illumina paired-end sequencing technology to elucidate the genes involved in flavonoid biosynthesis pathways. The de novo assembly of high-quality paired-end reads resulted in ~2.3 million high-quality reads with a pooled transcript of 45,647 comprising ~76Mb transcriptome with a mean length (bp) of 1,674 and N50 of 1,868bp. Furthermore, the coding sequence (CDS) prediction analysis from 45,647 pooled transcripts resulted in 45,444 CDS with a total length and mean length of 76,398,686 and 1,674, respectively. The Gene Ontology (GO) analysis resulted in a high number of CDSs assigned to 25,342 GO terms, which grouped the predicted CDS into three main domains, i.e., Biological Process (19,550), Molecular Function (19,873), and Cellular Component (14,577). The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database was used to categorize 6,353 CDS into 25 distinct biological pathway categories, in which the majority of mapped CDS were shown to be related to translation (645), followed by signal transduction (532), carbohydrate metabolism (524), folding, sorting, and degradation (522). Among these, only ~ 64 and 14 CDSs were found to be involved in the phenylpropanoid and flavonoid biosynthesis pathways, respectively. Quantitative Real-time PCR was used to check the expression profile of fourteen potential flavonoid biosynthesis pathway genes. The qRT-PCR analysis result matches the transcriptome sequence data validating the Illumina sequence results. Moreover, a large number of genes associated with the flavonoids biosynthesis pathway were found to be upregulated under the induction of methyl jasmonate. The present-day study on transcriptome sequence data of A. racemosus can be utilized for characterizing genes involved in flavonoid biosynthesis pathways and for functional genomics analysis in A. racemosus using the reverse genetics approach (CRISPR/Cas9 technology).